High Strength Conductive Composites with Plasmonic Nanoparticles Aligned on Aramid Nanofibers. (21st October 2016) - Lyu, Jing; Wang, Xinzhi; Liu, Lehao; Kim, Yoonseob; Tanyi, Ekembu K.; Chi, Hang; Feng, Wenchun; Xu, Lizhi; Li, Tiehu; Noginov, Mikhail A.; Uher, Ctirad; Hammig, Mark D.; et al.
Abstract : Rapidly evolving fields of biomedical, energy, and (opto)electronic devices bring forward the need for deformable conductors with constantly rising benchmarks for mechanical properties and electronic conductivity. The search for conductors with improved strength and strain have inspired the multiple studies of nanocomposites and amorphous metals. However, finding conductors that defy the boundaries of classical materials and exhibit simultaneously high strength, toughness, and fast charge transport while enabling their scalable production, remains a difficult materials engineering challenge. Here, composites made from aramid nanofibers (ANFs) and gold nanoparticles (Au NPs) that offer a new toolset for engineering high strength flexible conductors are described. ANFs are derived from Kevlar macrofibers and retain their strong mechanical properties and temperature resilience. Au NPs are infiltrated into a porous, free‐standing aramid matrix, becoming aligned on ANFs, which reduces the charge percolation threshold and facilitates charge transport. Further thermal annealing at 300 °C results in the Au‐ANF composites with an electrical conductivity of 1.25 × 10 4 S cm −1 combined with a tensile strength of 96 MPa, a Young's modulus of 5.29 GPa, and a toughness of 1.3 MJ m −3 . These parameters exceed those of most of the composite materials, and are comparable to those of amorphous metals but have no volume limitations. The plasmonic optical frequencies characteristic for constituent NPs are present in the composites with ANFs enabling plasmon‐based optoelectronic applications. Abstract : A composite based on aramid nanofibers and gold nanoparticles reveals high mechanical properties and conductivity, being competitive with the best nanocomposites and amorphous metals. Gold nanoparticles are self‐assembled in chains on aramid nanofibers, which reduces the percolation threshold. Thermal annealing further facilitates charge transport. The scalable fabrication of the free‐standing composites sheets leads to ground‐breaking materials for wearable electronics and plasmonics.